2021
DOI: 10.1063/5.0033874
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effect for an effective attraction between like-charged macroions immersed in an electrolyte solution: The intensification mechanism of the effective attraction caused by the translational motion of solvent particles

Abstract: The effective interaction between macroanions immersed in an electrolyte solution was calculated using an integral equation theory of liquids to study the solvent granularity effect on the effective attraction mediated by cations. Explicit and implicit solvent models were examined. The effective attraction for the explicit solvent model was found to be stronger than that for the implicit solvent model. This solvent effect was remarkably enhanced only when the effective attraction between macroanions was strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Because the calculation cost for "Model A", that was mentioned above, was too expensive, the solvent hard spheres and the macroanions were removed from it. The results calculated using the HNC closure showed that the solvent hard spheres intensify the effective attraction between like-charged particles [40,41]. However, the explicit solvent model was not required, and the implicit solvent model also showed the effective attraction and the reentrant behavior in our studies [40,41].…”
Section: Model Bmentioning
confidence: 61%
See 4 more Smart Citations
“…Because the calculation cost for "Model A", that was mentioned above, was too expensive, the solvent hard spheres and the macroanions were removed from it. The results calculated using the HNC closure showed that the solvent hard spheres intensify the effective attraction between like-charged particles [40,41]. However, the explicit solvent model was not required, and the implicit solvent model also showed the effective attraction and the reentrant behavior in our studies [40,41].…”
Section: Model Bmentioning
confidence: 61%
“…[44], the IPY2-OZ theory gave reasonable correlation functions for highly associating ionic systems such as the 2:2 electrolytes, whereas for monovalent ionic systems the HNC-OZ theory was known to be reasonable [41,45,46]. The model adopted in this study was a mixture of monovalent and multivalent ions, which is an intermediate system between the above-mentioned references [41,[44][45][46]. Moreover, this study has dealt with the effective attraction between like-charged particles, which was not considered in the previous studies [41,[44][45][46].…”
Section: Results and Discussion -mentioning
confidence: 97%
See 3 more Smart Citations